Structural testing of wooden aircraft - College of Aeronautics, (Cranfield) (College of Aeronautics, 1964)
For some years now the structural integrity of wooden aircraft of timber and glued plywood torsion box construction has been a matter of concern to the Air Registration Board since it is impossible to assess, by inspection, the strength of an apparently sound glued joint. A programme of testing two representative specimens of two types of aircraft was therefore agreed by the Ministry of Aviation and carried out by the College in conjunction with the Air Registration Board. This report deals with the factual aspects of these tests which were conducted during the period December 1963/February 1964 in the Structural Testing Laboratory of the Department of Aircraft Design.